EVALUASI TINGKAT KETERAMPILAN SEPAK TAKRAW PADA ATLET PPLPD ACEH TAHUN 2019 - Taufiqul Khaliq; Masri Masri (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
During training researchers saw athletes perform service techniques that did not pass the net, imperfect recieve techniques ,weak smash techniques and not even on target often also did not pass the net, feed techniques that were not so perfect that the killer could not smash, did not dare block so that the ball entered easily. Football skills play a very important role in a match and the success of training in a training center. The purpose of the study was to find out the level of takraw football skills in PPLPD Aceh athletes in 2019. The population of this study was Pplpd Aceh athletes and the study subjects numbered 8 people with total sampling techniques. Data collection is done by takraw football skills test consisting of Service, Receive, Smash, Feed, Block. The data obtained by youth was analyzed using statistical techniques in the form of percentages and category helpers. In conclusion, the mean value of service skills is 34.87 in the